Clinical outcomes of adolescents and young adults with advanced solid tumours participating in phase I trials. (September 2018) - Sundar, Raghav; McVeigh, Terri; Dolling, David; Petruckevitch, Ann; Diamantis, Nikolaos; Ang, Joo Ern; Chenard-Poiriér, Maxime; Collins, Dearbhaile; Lim, Joline; Ameratunga, Malaka; Khan, Khurum; Kaye, Stan B.; et al.
Abstract: Background: Adolescent and young adult (AYA) patients with advanced solid tumours are often considered for phase I clinical trials with novel agents. The outcome of AYAs in these trials have not been described before. Aim: To study the outcome of AYA patients in phase I clinical trials. Methods: Clinical trial data of AYAs (defined as aged 15–39 years at diagnosis) treated at the Drug Development Unit, Royal Marsden Hospital, between 2002 and 2016, were analysed. Results: From a prospectively maintained database of 2631 patients treated in phase I trials, 219 AYA patients (8%) were identified. Major tumour types included gynaecological cancer (25%) and sarcoma (18%). Twenty-five (11%) had a known hereditary cancer syndrome (most commonly BRCA). Molecular characterisation of tumours (n = 45) identified mutations most commonly in TP53 (33%), PI3KCA (18%) and KRAS (9%). Therapeutic targets of trials included DNA damage repair (16%), phosphoinositide 3-kinase (PI3K) (16%) and angiogenesis (16%). Grade 3/4 toxicities were experienced in 26% of patients. Of the 214 evaluable patients, objective response rate was 12%, with clinical benefit rate at 6 months of 22%. Median overall survival (OS) was 7.5 months (95% confidence interval: 6.3–9.5), and 2-year OS was 11%. Of patients with responses, 36% were matched to phase I trials based on germline or somatic genetic aberrations. Conclusion: We describe the outcome of the largest cohort of AYA patients treated in phase I trials. A subgroup of these patients demonstrates benefit, with several durable responses beyond 2 years. A sizeable proportion of AYA patients have cancer syndromes, significant family history or somatic molecular aberrancies which may influence novel therapeutic treatment options. Highlights: Outcomes of the largest cohort of adolescents and young adults (AYAs) in phase I clinical trials reported. Durable responses and prolonged survival described in a subgroup of patients. Several AYA cancer patients have cancer syndromes or somatic genetic aberrancies.